Customs as facilitation of trade: Case of Albania - Etleva Bajrami; Gentiana Sharku (Contemporary Economics, 2010)
Economic cooperation and trade between countries of region is very important as a opening step for entering in big markets like EU-s. All agreements have a huge impact in customs administration for elimination of customs taxes and for facilitation of trade during customs crossing. Trade integration is seen as faster way for countries to complete all necessary condition for European Integration. This process requires fulfillment of all reforms, needed for approaches the development and integration between countries. This process is spread in time because of the feature and difference between society and their economies. Regional economic integration is considered an import component for longterm integration of South Eastern European countries in EU. Membership of Albania in WTO brings a number of free trade agreements, with the main purpose trade liberalization. The essences of these agreements have been liberalization of customs tariffs for increasing foreign trade and attract foreign investors. The loss of customs income will be compensating from imports increasing and economic development in general. The role of Customs has changed from one of a complete focus on revenue collection to a broad role encompassing components of revenue collection, trade facilitation and border security. Simplified customs procedures and documents are very important for improving relation of business and government and also improving business performance. The aim of this paper is to point out the roles, responsibilities and challenges of customs, for concluding this we have conducted a survey for analyzing the performance of customs in Albania.
Keywords: 330